Laser Wavelength Estimation Method Based on a High-Birefringence Fiber Loop Mirror - Alvarez Tamayo, Ricardo Iván; Prieto Cortés, Patricia; Durán Sánchez, Manuel; Ibarra Escamilla, Baldemar; Barcelata Pinzón, Antonio; Kuzin, Evgeny A. (2019)
A simple method for the estimation of the wavelength of a fiber laser system is proposed. The method is based on the use of a high-birefringence-fiber loop mirror (HBFLM). The HBFLM exhibits a periodic transmission/reflection spectrum whose spectral characteristics are determined by the length and temperature of the high-birefringence fiber (HBF). Then, by the previous characterization of the HBFLM spectral transmission response, the central wavelength of the generated laser line can be estimated. By using a photodetector, the wavelength of the laser line is estimated during an HBF temperature scanning by measuring the temperature at which the maximum transmitted power of the HBFLM is reached. The proposed method is demonstrated in a linear cavity tunable Er/Yb fiber laser. This method is a reliable and low-cost alternative for laser wavelength determination in short wavelength ranges without the use of specialized and expensive equipment